Short-term effects of modest salt reduction combined with DASH diet on changing salt eating habits in hypertensive patients with type II diabetes. (18th August 2022) - Chen, Dan; Tang, Jie; Gong, Tao; Mu, Lisha; Li, Jing; Yu, Pingping; Wang, Hao; Bu, Xiaoqing; Mu, Lihong; Mei, Ying
ABSTRACT: Objective: Excessive salt intake is currently the foremost universal risk factor for controllable chronic disease. This study evaluated the short-term effects of a modest salt intake reduction combined with the Chinese Modified Dietary Approaches to Stop Hypertension (CM-DASH) diet on sodium and potassium intake, mean arterial pressure (MAP), and pulse pressure (PP) in hypertensive patients with type II diabetes. Methods: Sixty-one participants were randomized to the intervention group (52% low-sodium salt and DASH) and control group (normal salt and DASH). An 8-week dietary intervention was applied. Daily salt intake, blood pressure (BP), and drug use were recorded every week. Twenty-four-hour urine, casual urine, and blood samples were measured at baseline, the 4th week, and the end of the intervention. Results: Fifty-nine patients (25 men) completed the entire study. Sodium intake decreased by 1259.66 (792.76, 1726.56)/705.80 (149.21, 1262.39) mg/day after 4 weeks (intervention: P < .001; control: P = .015). Potassium intake increased by 641.14 (73.31, 1208.96)/43.43 (−259.66, 346.53) mg/day (intervention: P = .028); MAP decreased by 9.06 (6.69, 11.43)/7.16 (4.03, 10.28) mmHg (both: P < .001); PP decreased by 7.97 (3.05, 12.88)/5.74 (2.55, 8.94) mmHg (intervention: P = .002; control: P = .001) after 8 weeks. However, the difference between the two groups was not statistically significant. Conclusion: Modest salt reduction and the CM-DASH diet for hypertensive patients with type II diabetes can achieve short-term salt reduction effects. The effect on changing salt-eating habits needs to be investigated with an extended follow-up.